Gustave Doré : twelve comic strips - Doré, Gustave (University Press of Mississippi, 2015)
Cover -- Contents -- Preface -- Introduction -- Bibliography -- THE COMIC STRIPS -- 1. Les Travaux d'Hercule (The Labors of Hercules) -- Album, 1847 -- 2. Le Communisme en tableau (Communism Depicted) -- Journal pour Rire, 1848 -- 3. La Vie en Province, Histoire d'une invitation à la campagne (Life in the Provinces, Story of an Invitation to the Countryside) -- Journal pour Rire, 1849 -- 4. L'Homme aux Cent Mille Écus (The Man with One Hundred Thousand Crowns) -- Journal pour Rire, 1850